Effect of fertilization in water quality and in zooplankton community in open plankton-culture ponds - Sipauba Tavares, Lucia Helena [UNESP]; Santeiro, Rachel Magalhaes [UNESP]; Pinto Coelho, Ricardo Motta; Braga, Francisco Manoel de Souza [UNESP] (Universidade Federal de Uberlândia (UFU), 2009)
The effect of swine manure fertilization on the water quality of zooplankton artificial culture in two ponds was measured in diel cycles on different months (October 1999, January and March 2000). Fertilization affected directly water quality; values for total phosphorus were above 1.4 mgL(-1) and maximum rates for ammonia reached 108 mu gL(-1). Zooplankton community comprised four species, namely, Brachionus calyciflorus, B. falcatus, Moina sp. and Thermocyclops sp. B. falcatus (Rotifera) and Moina sp (Cladocera) were dominant respectively in January and in March. There was no difference in abundance of zooplankton between the two ponds (p>0.05), although adult cyclopoid Thermocyclops sp was different between diel cycles (p<0.05). There were significant differences (p<0.05) in dissolved oxygen, ammonia, total phosphorus, orthophosphate, nitrite and nitrate between ponds. In fact, only dissolved oxygen and pH were significantly different (p<0.05) between the ponds' surface and bottom. Organic fertilization also provided greater amount of nutrients and higher pH and conductivity, coupled to greater oscillations in the concentration of dissolved oxygen, directly affecting the zooplanktonic composition.
Efeito da fertilização na qualidade da água e na comunidade zooplanctônica em tanques externos de cultivo de plâncton
Keywords: Pond; Water quality; Zooplankton; Manure; Management